Between the Existential Angst and the Absurdist Quest: Samuel Beckett's Waiting for Godot and the Search for Meaning - Hassan, Sameer Abd Al hussein (Celebes Scholar pg, 2024)
This paper explores the existential themes present in Samuel Beckett's iconic play, Waiting for Godot. The paper aims to unravel the existential intricacies and complexities of meaning and purpose in a world devoid of both through the lens of Albert Camus' absurdist philosophy and Jean-Paul Sartre's existentialist philosophy. The play explores into the realm of the absurd, compelling the audience to confront the existential nature of existence and actively pursue significance. The protagonists' persistent inquiry and pursuit of significance mirror the existentialist notion of constructing personal purpose in a world devoid of inherent meaning. Through an analysis of the characters, dialogue, and setting, the paper illuminates the ways in which Beckett's work reflects and challenges existential ideas, ultimately offering a deeper understanding of the human condition and the quest for meaning.